Periocular dermatoses - P. Chang, MD; G. Moreno-Coutiño, MD (Wolters Kluwer, 2017)
The periocular area may be affected by infectious or noninfectious diseases such as inflammatory dermatoses, systemic disease, drug reactions, benign and malignant lesions, traumatic lesions, and esthetic complications. We present a review of the most common periocular dermatoses.